2017
DOI: 10.1371/journal.pone.0178828
|View full text |Cite
|
Sign up to set email alerts
|

Haplotypes on pig chromosome 3 distinguish metabolically healthy from unhealthy obese individuals

Abstract: We have established a pig resource population specifically designed to elucidate the genetics involved in development of obesity and obesity related co-morbidities by crossing the obesity prone Göttingen Minipig breed with two lean production pig breeds. In this study we have performed genome wide association (GWA) to identify loci with effect on blood lipid levels. The most significantly associated single nucleotide polymorphisms (SNPs) were used for linkage disequilibrium (LD) and haplotype analyses. Three s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…Since Göttingen Minipigs are able to expand the fat compartments without compromising adipose tissue metabolism it might be hypothesized that naturally occurring fatty acids activate PPARG in the liver of the FFC diet treated pigs, mimicking treatments with TDZs, resulting in repartitioning of lipid from liver to adipose tissues. Our findings are in agreement with a previous study showing that haplotypes segregating from Göttingen Minipigs can uphold a healthy lipid profile despite development of obesity indicating they have a phenotype comparable to the MHO phenotype in humans 14 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Since Göttingen Minipigs are able to expand the fat compartments without compromising adipose tissue metabolism it might be hypothesized that naturally occurring fatty acids activate PPARG in the liver of the FFC diet treated pigs, mimicking treatments with TDZs, resulting in repartitioning of lipid from liver to adipose tissues. Our findings are in agreement with a previous study showing that haplotypes segregating from Göttingen Minipigs can uphold a healthy lipid profile despite development of obesity indicating they have a phenotype comparable to the MHO phenotype in humans 14 .…”
Section: Discussionsupporting
confidence: 93%
“…We have previously provided evidence of genetic predisposition for an MHO-like phenotype in Göttingen Minipigs 14 . In this study, we have performed highthroughput qPCR on genes of relevance for metabolism in liver, subcutaneous adipose (SAT) and visceral adipose tissues (VAT) to characterize the transcriptional changes underlying the alterations observed in these tissues in Göttingen Minipigs fed chow, FFC diet, or FFC diet on a background of streptozotocin-induced diabetes for 13 months.…”
Section: Introductionmentioning
confidence: 99%
“…An example of how the statistical analyses can be conducted includes: (1) subgroup identification across headache categories by means of multidimensional scaling, factor analysis and/or cluster analysis (eg, hierarchical cluster analysis, k ‐means clustering, latent class analysis, and fuzzy cluster models) and (2) statistical model fitting, eg, of the biochemical compound concentration as a response variable and the headache category, subgroup and confounding factors (eg, sex and age) as explanatory variables while considering the risk of overfitting …”
Section: Subgroup Identification Based On Profilesmentioning
confidence: 99%
“…An example of how the statistical analyses can be conducted includes: (1) subgroup identification across headache categories by means of multidimensional scaling, factor analysis and/or cluster analysis (eg, hierarchical cluster analysis, k -means clustering, latent class analysis, and fuzzy cluster models) [20][21][22] and (2) statistical model fitting, eg, of the biochemical compound concentration as a response variable and the headache category, subgroup and confounding factors (eg, sex and age) as explanatory variables while considering the risk of overfitting. [23][24][25][26] Data dimensionality and complexity should be considered during sample size determination. Sample size determination for metabolic phenotypic studies seem to require use of other estimation procedures than those traditionally applied as well as initial conduct of a pilot study.…”
Section: Subgroup Identification Based On Profilesmentioning
confidence: 99%
“…Therefore, several breeds of pigs, including Ossabaw and Göttingen Minipigs (GM) have been extensively used as animal models for MS and obesity. Specifically, we have worked with the GM breed as an obesity model, providing evidence of a genetic predisposition for an MHO-like phenotype in this breed (Frederiksen et al, 2017 ). We have further shown that GM fed a high fat diet become obese but do not develop hepatic steatosis (Schumacher-Petersen et al, 2019 ), and that severely obese GM have a large capacity for adipose tissue expansion and are protected against many of the metabolic and hepatic abnormalities associated with obesity (Cirera et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%